CONTEMPORARY METHODS OF DESCRIPTIVE GEOMETRY IN CONSTRUCTION ARCHITECTURE AND ENGINEERING: INNOVATIONS AND APPLICATIONS - Yuldashev Salmonxon Iqboljon ugli (Bright Mind Publishing, 2025)
Descriptive Geometry forms the mathematical and visual foundation for architecture and engineering, enabling the accurate representation, analysis, and manipulation of three-dimensional structures. Recent advancements in computational methods, parametric modeling, and algorithmic design have transformed traditional approaches, integrating digital tools that enhance precision, efficiency, and creative exploration. This study investigates contemporary methods of Descriptive Geometry in construction architecture and engineering, emphasizing their theoretical underpinnings, computational techniques, and practical applications. Following the IMRaD framework, the research combines a systematic literature review, case studies of digital modeling workflows, and experimental application in structural and architectural projects. Results demonstrate that modern approaches—including parametric modeling in Rhino, algorithmic design via Grasshopper, BIM integration, and 3D simulation—significantly improve structural accuracy, optimize resource usage, and expand design possibilities. The discussion situates these findings within broader trends in digital architecture, engineering education, and computational design, highlighting both opportunities and challenges associated with adopting contemporary methods. The conclusion emphasizes that integrating modern Descriptive Geometry techniques equips architects, engineers, and students with essential competencies for innovation, sustainability, and precision in construction practice.
Keywords: Descriptive Geometry, Construction Architecture, Engineering, Parametric Modeling, BIM, Computational Design, 3D Simulation, Algorithmic Methods.